ANALISIS PROBLEMATIKA MUTU PENDIDIKAN TINGKAT DASAR BERDASARKAN HASIL AKREDITASI DI KABUPATEN KUANTAN SINGINGI - Johan Andriesgo; Haris Riadi; Joni Hendra K (JURNAL AL-TANZIM, 2020)
This research aims to find out about the problems of education quality faced by SD / MI in Kuantan Singingi Regency based on the results of the 2019 accreditation. The research was revealed in 97 schools/madrasah at SD/MI.  It was designed as a qualitative descriptive research. Data were collected through interview, observation, and documentation. The findings show that the problems faced by schools/madrasah based on the achievements of the accreditation results in 2019 are on fulfilling the standards of educators, education personnel, educational facilities and infrastructure standards. Fulfillment of the standards of educators and educational staff including those related to academic qualifications of educators, educators’ certificates ownership, teachers’ educational suitability background and their teaching staff adequacy. Whereas the standard of facilities and infrastructure are related to the completeness of facilities and infrastructure such as: teacher's room, library, UKS, circulation, canteen ownership, and learning aids.